Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Itik Panggang Pada Warung Makan - Karlina Karlina; Ainun Ainun; Fathul Jannah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The aim of this research is to determine the influence of the marketing mix on the decision to purchase roast duck at Warung Makan. From the results of the validity test of 28 valid statements and the significant limit of rtable is 0.05 and the two-sided test, the rtable value is 0.2787 while rcount > rtable for each statement in this study. The results of the reliability test, the Cronbach Alpha value is 0.920, the N of items is 28. From the results of data analysis and data tabulation, it can be seen that the results of the regression equation are Y= 0.773+0.380X1-0.098X2+0.423X3+0.103X4. Based on the calculation results, the R value (correlation coefficient) of 0.654 is obtained at a relationship level of 0.60 – 0.799, which means it is at a strong relationship level between the product (X1), price (X2), place (X3) and promotion (X4) variables. ) on purchasing decisions (Y). The Adjusted R Square value (coefficient of determination) is 0.376 or 37.6%. This shows that the variables product (X1), price (X2), place (X3), and promotion (X4) contribute or contribute an influence of 37.6% to the purchasing decision (Y) of roast duck at Warung Makan, while the remaining amount is 62.4% is influenced by other variables not included in this study. The Fcount test results obtained a value of 8.392 with a significance level of 0.000 while the Ftable value was 2.58 (4:45). So Fcount is 8.329 > Ftable value is 2.58. This means that there is a joint influence between product variables (X1), price (X2), place (X3), and promotion (X4) on purchasing decisions (Y). The results of the t test obtained a Product tcount value (X1) of tcount 2.473 > ttable 2.01410 with a significance level of 0.017 < 0.05. So H0 is rejected and Ha is accepted. Price (X2) t is -0.728 < t table is 2.01410 with a significance level of 0.471 > 0.05. So H0 is accepted and Ha is rejected. Place (X3) tcount is 1.874 < ttable is 2.01410 with a significance level of 0.067 > 0.05. So H0 is accepted and Ha is rejected. Promotion (X4) tcount is 0.511 < ttable is 2.01410 with a significance level of 0.612 > 0.05. So H0 is accepted and Ha is rejected. Based on SPSS results, the product variable (X1) has a dominant influence on purchasing decisions (Y) with a t value of 2.473 with a significant rate of 0.017.